2013
DOI: 10.1162/jocn_a_00296
|View full text |Cite
|
Sign up to set email alerts
|

fMRI Investigation of Monocular Pattern Rivalry

Abstract: In monocular pattern rivalry, a composite image is shown to both eyes. The patient experiences perceptual alternations in which the two stimulus components alternate in clarity or salience. We used fMRI at 3T to image brain activity while participants perceived monocular rivalry passively or indicated their percepts with a task. The stimulus patterns were left/right oblique gratings, face/house composites, or a nonrivalrous control stimulus that did not support the perception of transparency or image segmentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
1
3
0
Order By: Relevance
“…We presume that similar modulations according to dominance/suppression might be observed for PR if the stimulus components (i.e., red vs. green gratings) not eyes were differentially tagged, and this is planned in a future study. However, we predict that the magnitude of modulations may be still smaller for PR because of the lack of eye-based competition [40, 59], and consistent with previous findings that binocular rivalry is stronger than other types of rivalry [44, 60].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We presume that similar modulations according to dominance/suppression might be observed for PR if the stimulus components (i.e., red vs. green gratings) not eyes were differentially tagged, and this is planned in a future study. However, we predict that the magnitude of modulations may be still smaller for PR because of the lack of eye-based competition [40, 59], and consistent with previous findings that binocular rivalry is stronger than other types of rivalry [44, 60].…”
Section: Discussionsupporting
confidence: 91%
“…The lateral occipital cortex has been strongly associated with figure/ground organization, visual segmentation and grouping, e.g. [59, 77]. 2.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that modulation of stimulus‐specific activity in occipital/temporal areas 150–270 ms after stimulus onset possibly reflected inhibition of the suppressed image . It may also be relevant that several studies have found robust modulation of ventral stream regions selective for faces or objects when suppressed percepts are contrasted with dominant (e.g., de Jong et al, 2020; Mendola & Buckthought, 2013; Sterzer & Rees, 2008; Tong et al, 2006; see also Zhan et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, preferential saccades toward an upright face take place within 100-140 ms following presentation (Kirchner and Thorpe, 2006; Crouzet et al, 2010), demonstrating that detection of an upright face occurs quite early in visual processing. Neural correlates of face recognition have been extensively examined using functional MRI (fMRI) (Puce et al, 1995; Kanwisher et al, 1997; Summerfield et al, 2006; Mendola et al, 2013) and electrocorticography (ECoG) (Miller et al, 2009; Engell and McCarthy, 2010; Vidal et al, 2010). These studies have consistently localized regions of face-selectivity around the fusiform gyrus and around the inferior occipital gyrus.…”
Section: Introductionmentioning
confidence: 99%